SOCIAL MEDIA AND INTERPERSONAL SKILL DEVELOPMENT: EXPLORING GENERATION Z’S SOCIAL DYNAMICS - Baharuddin, Fathonah Aina; Ismail, Siti Anis Aimi; Shukor, Muhammad Fadzil Ahmad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Generation Z has integrated social media into their daily routines, making it a platform for communication, self-expression, and connection. Social media has significantly influenced the way Gen Z communicates. The stigma surrounding Generation Z, primarily due to the heavy usage of social media, is becoming a worrying issue, as it is perceived to lack social skills. This study aims to examine the relationship between social media usage and its impact on interpersonal communication among Generation Z, identify the connection between self-esteem and interpersonal skills in social media, and explore interaction skills on social media and their effect on interpersonal abilities. Additionally, Generation Z can enhance interpersonal skills and foster communication across various groups through social media, as well as build relationships and exchange ideas. A total of 305 students from Universiti Teknologi MARA (UiTM) completed the questionnaire. The analysis involved descriptive statistics and correlation analysis, with results displayed in tables illustrating the relationships between the studied components. The findings indicated that social media usage influenced Generation Z's patterns, self-esteem, and social skills, using Social Identity Theory (SIT), which examines how individuals identify as members of a community.